PENINGKATAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS DAN SELF-CONFIDENCE SISWA SMA MELALUI STRATEGI PEMBELAJARAN THINK, TALK, WRITE (TTW) DENGAN MIND MAPPING - Widia Siti Prayudi; Taufik Rahman (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2021)
Mathematical creative thinking ability is very important in life and all the problems that exist in it by obtaining, managing and utilizing information. To achieve mathematical creative thinking ability, requires the strong character one of which is self-confidence. However in reality mathematical creative thinking ability and self-confidence of students in Indonesia is still low. One alternative learning to improve mathematical creative thinking ability and self-confidence is the Think, Talk, Write (TTW) with Mind Mapping learning strategy. The purpose of this study are: 1) To find out the increase in mathematical creative thinking abilities of students who obtain TTW strategies with Mind Mapping is higher than students who obtain conventional learning models; 2) To find out the achievement of self-confidence of students who obtain TTW strategies with Mind Mapping is better than students who obtain conventional learning models; 3) To find out whether there is a positive correlation between mathematical creative thinking abilities and self-confidence of students who obtain TTW strategy with Mind Mapping. The method used in this study is a quasi-experimental method with a pretest-posttest control group experimental design. The population of this study was tenth grade students of High School No. 15 Bandung. The sampling technique was purposive sampling, using two classes, namely the control class and the experimental class. Based on the results of data analysis, the following conclusions are obtained: 1) The increase in mathematical creative thinking abilities of students who obtain TTW strategies with Mind Mapping is higher than students who obtain conventional learning models; 2) Self-confidence of students who obtain TTW strategies with Mind Mapping is better than with students who obtain conventional learning models; 3) There is a positive correlation between mathematical creative thinking ability and students' self-confidence who obtained the TTW strategy with Mind Mapping. Keywords: Mathematical Creative Thinking, Self-Confidence, TTW, mind mapping